Effect of planting density on the performance of boro rice (BRRI dhan28) (Bangladesh Agronomy Journal, 2015)
A field experiment was conducted at the Agrotechnology Field Laboratory of Khulna University during the boro season to evaluate the effect of planting density on the performance of rice variety BRRI dhan28. The experiment received twelve treatments, which were divided into two distinct patterns - single row and paired row. The single row had four treatments and paired row had eight treatments. Planting densities were 40, 27, 20 and 16 hills m-2. The experiment was arranged in a randomized complete block design (RCBD) with three replications. Standard management practices were followed in raising crops. Results revealed that closer spacing produced higher yields where 40 hills m-2 produced the most (4.81 t ha-1), which was statistically similar with that of 27 hills   m-2. Paired row planting showed better performance than single row planting. Plant height, grains panicle-1, sterile spikelets panicle-1, 1000-grain weight, grain yield were found better in paired row planting. Paired row planting at a spacing of (35 cm + 15 cm) × 10 cm  i.e row to row distance is 35 cm & 15 cm and hill to hill distance is 10 cm; found the highest grain yield (4.81 t ha-1) and the lowest yield (2.97 t ha-1) was found in single row using a spacing of 25 cm × 25 cm.Bangladesh Agron. J. 2014, 17(2): 67-76